Performance of a non-contact infrared thermometer in healthy newborns. Issue 3 (16th March 2016) - Sollai, Sara; Dani, Carlo; Berti, Elettra; Fancelli, Claudia; Galli, Luisa; de Martino, Maurizio; Chiappini, Elena
Abstract : Objective: To evaluate the performance of a non-contact infrared thermometer (NCIT) in comparison with digital axillary thermometer (DAT) and infrared tympanic thermometers (ITT) in a population of healthy at term and preterm newborns nursed in incubators. Setting: 1 level III maternity hospital, and its intensive neonatal care unit. Participants: 119 healthy at term newborns and 70 preterm newborns nursed in incubators were consecutively enrolled. Exclusion criteria were unstable/critical conditions, polymalformative congenital syndromes and severe congenital syndromes. Interventions: Body temperature readings were prospectively collected. Each participant underwent bilateral axillary temperature measurement with DAT, bilateral tympanic measurement with ITT and mid-forehead temperature measurements using NCIT. Primary outcome measures: Degree of agreement between methods was evaluated by the Bland and Altman method. Results: 714 measurements in 119 healthy at term newborns and 420 measurements in 70 preterm newborns nursed in incubators were performed. Clinical reproducibility of NCIT was 0.0455°C for infants in incubators and 0.0861°C for infants outside an incubator. Bias was 0.029°C for infants in incubators and <0.0001°C for infants outside an incubator. Zero outliers were recorded. The mean difference between methods was good both for newborns at term (0.12°C for NCIT vs DAT and 0.02°C for NCIT vs ITT) and preterm newborns in incubators (0.10°C for NCIT vs DAT and 0.14°C for NCIT vs ITT). Limits of agreement were 0.99 to −0.75 and 0.78 to −0.75 in at term newborns and were particularly satisfactory in preterm newborns in incubators (95% CI: 0.48 to −0.27 and 0.68 to −0.40). Conclusions: Our results with Bland and Altman analysis demonstrate that NCIT is a very promising tool, especially in preterm newborns nursed in incubators. Trial registration: The study was approved by the Careggi University Hospital Ethics Committee (07/2011).